The M3 muscarinic receptor is required for optimal adaptive immunity to helminth and bacterial infection. - Matthew Darby; Corinna Schnoeller; Alykhan Vira; Fiona Jane Culley; Saeeda Bobat; Erin Logan; Frank Kirstein; Jürgen Wess; Adam F Cunningham; Frank Brombacher; Murray E Selkirk; William G C Horsnell (PLoS Pathogens)
Innate immunity is regulated by cholinergic signalling through nicotinic acetylcholine receptors. We show here that signalling through the M3 muscarinic acetylcholine receptor (M3R) plays an important role in adaptive immunity to both Nippostrongylus brasiliensis and Salmonella enterica serovar Typhimurium, as M3R-/- mice were impaired in their ability to resolve infection with either pathogen. CD4 T cell activation and cytokine production were reduced in M3R-/- mice. Immunity to secondary infection with N. brasiliensis was severely impaired, with reduced cytokine responses in M3R-/- mice accompanied by lower numbers of mucus-producing goblet cells and alternatively activated macrophages in the lungs. Ex vivo lymphocyte stimulation of cells from intact BALB/c mice infected with N. brasiliensis and S. typhimurium with muscarinic agonists resulted in enhanced production of IL-13 and IFN-γ respectively, which was blocked by an M3R-selective antagonist. Our data therefore indicate that cholinergic signalling via the M3R is essential for optimal Th1 and Th2 adaptive immunity to infection.